2010
DOI: 10.1503/jpn.090017
|View full text |Cite
|
Sign up to set email alerts
|

Differential patterns of initial and sustained responses in amygdala and cortical regions to emotional stimuli in schizophrenia patients and healthy participants

Abstract: 41Background: We sought to investigate the altered brain responses to emotional stimuli in patients with schizophrenia. Methods: We ana lyzed data from 14 patients with schizophrenia and 14 healthy controls who performed an emotional face matching task. We evaluated brain activity and connectivity in the amygdala and cortical regions during the initial (first 21 seconds of each stimulation block) and sustained (last 21 seconds) stages of an emotional processing task, and we determined changes in amygdala activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
0
9
1
1
Order By: Relevance
“…Patients might also have used a cognitive compensatory strategy favouring accuracy over speed to maintain performance; this strategy has been involved in the improvement of several cognitive processes in patients with schizophrenia. [30][31][32] However, our results suggest that mentalizing was slowed down in patients with schizophrenia, even when executive contextual control was taken into account. Many studies have reported increased response times during ToM tasks in patients with schizophrenia, [33][34][35] although the specificity of this slowdown to the domain of social cognition has remained unclear.…”
Section: Slowdown Of Intention Processing In Patients With Schizophreniacontrasting
confidence: 56%
“…Patients might also have used a cognitive compensatory strategy favouring accuracy over speed to maintain performance; this strategy has been involved in the improvement of several cognitive processes in patients with schizophrenia. [30][31][32] However, our results suggest that mentalizing was slowed down in patients with schizophrenia, even when executive contextual control was taken into account. Many studies have reported increased response times during ToM tasks in patients with schizophrenia, [33][34][35] although the specificity of this slowdown to the domain of social cognition has remained unclear.…”
Section: Slowdown Of Intention Processing In Patients With Schizophreniacontrasting
confidence: 56%
“…Contrasts of responses of each facial expression to shapes were generated for each subject, and then entered into a second-level general linear model treating subject as a random effect (random effects analysis). We utilized the analysis strategy used by multiple previous studies ( 52 57 ) to explore the potential specific signature effects of each of the threat faces (fearful and angry) as well as neutral faces separately contrasted to the shapes condition (angry > shapes, fearful > shapes, neutral > shapes). Our approach to model each facial expression (contrasted with shapes) allows us to examine effects of treatment on each face type, and is less potentially ambiguous than using a contrast of emotional faces > neutral faces.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors have found that patients show reduced activation of the amygdala in response to emotional face stimuli, which could be interpreted as an impairment in the processing of affective information [ 5 , 6 ]. On the other hand, others have shown normal activation or even hyperactivation of the amygdala, indicating that patients may suffer from hypersensitivity to emotional faces [ 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%